Initiation of Combustion of a Gel-Like Condensed Substance by a Local Source of Limited Power; Journal of Engineering Physics and Thermophysics; Vol. 90, iss. 1 - Glushkov D. O. Dmitry Olegovich (2017, 2017)
Title screen